Dysregulated Hypothalamic–Pituitary–Adrenal Axis Function Contributes to Altered Endocrine and Neurobehavioral Responses to Acute Stress - Kinlein, Scott A.; Wilson, Christopher D.; Karatsoreos, Ilia N. (Frontiers in Psychiatry, 2015)
Organisms react to environmental challenges by activating a coordinated set of brain-body responses known as the stress response. These physiological and behavioral countermeasures are, in large part, regulated by the neuroendocrine hypothalamic-pituitary-adrenal (HPA) axis. Normal functioning of the HPA axis ensures that an organism responds appropriately to altered environmental demands, representing an essential system to promote survival. Over the past several decades, increasing evidence supports the hypothesis that disruption of the HPA axis can lead to dysregulated stress response phenotypes, exacting a physiological cost on the organism commonly referred to as allostatic load. Further, it has been recognized that high allostatic load can contribute to increased vulnerability of the organism to further challenges. This observation leads to the notion that disrupted HPA function and resulting inappropriate responses to stressors may underlie many neuropsychiatric disorders, including depression and anxiety. In the present set of studies we investigate the role of both the normally functioning and disrupted HPA axis in the endocrine, neural, and behavioral responses to acute stress. Using a model of non-invasive chronic corticosterone (CORT) treatment in mice, we show that dysregulating the normal function of the HPA leads to a mismatch between the hormonal and neural response to acute stress, resulting in abnormal behavioral coping strategies. We believe this model can be leveraged to tease apart the mechanisms by which altered HPA function contributes to neurobehavioral dysregulation in response to acute stress.